Pacing behavior development in adolescent swimmers: A large-scale longitudinal data analysis - Menting, S. G. P.; Post, A. K.; Nijenhuis, S. B.; Koning, R. H.; Visscher, C.; Hettinga, F. J.; Elferink-Gemser, M. T. (Medicine & Science in Sports & Exercise, 2023)
Purpose: This study aimed to use a large-scale longitudinal design to investigate the development of the distribution of effort (e.g., pacing) in adolescent swimmers, specifically disentangling the effects of age and experience and differentiating between performance levels in adulthood. Methods: Season best times and 50-m split times of 100- and 200-m freestyle swimmers from five continents were gathered between 2000 and 2021. Included swimmers competed in a minimum of three seasons between 12 and 24 yr old (5.3 ± 1.9 seasons) and were categorized by performance level in adulthood (elite, sub-elite, high-competitive; 100-m: n = 3498 (47% female); 200-m: n = 2230 (56% female)). Multilevel models in which repeated measures (level 1) were nested within individual swimmers (level 2) were estimated to test the effects of age, race experience, and adult performance level on the percentage of total race time spent in each 50-m section (P < 0.05). Results: In the 100-m, male swimmers develop a relatively faster first 50-m when becoming older. This behavior also distinguishes elite from high-competitive swimmers. No such effects were found for female swimmers. Conversely, more experienced male and female swimmers exhibit a slower initial 50-m. With age and race experience, swimmers develop a more even velocity distribution in the 200-m. Adolescent swimmers reaching the elite level adopt a more even behavior compared with high-competitive. This differentiation occurs at a younger age in female (>13 yr) compared with male (>16 yr) swimmers. Conclusions: Pacing behavior development throughout adolescence is driven by age-related factors besides race experience. Swimmers attaining a higher performance level during adulthood exhibit a pacing behavior that better fits the task demands during adolescence. Monitoring and individually optimizing the pacing behavior of young swimmers is an important step toward elite performance.